Characteristics of evaluation of auto transport services - Norkobilov Jakhongir, (THE INNOVATION ECONOMY, 2026)
The article reflects the emergence of vehicle evaluation and the stages of their development. Also, the characteristics and development of motor vehicle evaluation, the effective development of motor vehicle evaluation in terms of improving the quality of life of the population in the use of motor vehicles, increasing the level of reliability of the evaluation results, and the principle difference of motor vehicle evaluation from the evaluation of other types of objects were analyzed.